25.6k views
4 votes
If F(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f°g)(x)?

1 Answer

3 votes

Answer:

The composite function is


(f \circ g)(x) = 3x^2 + 5

Explanation:

Composite functions:

Suppose that we have two functions, f and g. Their composite is given by:


(f \circ g)(x) = f(g(x))

In this question:

We have that:


f(x) = 3x + 2


g(x) = x^2 + 1

The composite function is:


(f \circ g)(x) = f(g(x)) = f(x^2+1) = 3(x^2 + 1) + 2 = 3x^2 + 3 + 2 = 3x^2 + 5

The composite function is


(f \circ g)(x) = 3x^2 + 5

User Muarl
by
5.0k points